Morphometric and Histological Characteristics of Aceh Cattle (Bos indicus) Ovaries during the Estrous Cycle - M. Jalaluddin (Universitas Syiah Kuala, 2014)
The reproductive performances of aceh cattle in extreme environment is supported by its reproductive capacity system. This research wasconducted to study there productive system of aceh cattle by examining morphometric and histological characteristics of aceh cow ovaries duringthe estrous cycle. Fifteen Aceh mature cows during estrous cycle, with 200-300 kg of body weight were used in this study. Samples were takenfrom slaughter house in Banda Aceh Municipality, Aceh Province. The ovaries were observed morphometry, then fixed in Bouin solution andprocessed histologically. Ovaries were stained with hematoxylin and eosin to observe the morphometric characteristics of ovarian histology. Thedata obtained are presented in the form of tables and figures, and analyzed descriptively. Aceh has a cow ovarian morphometry and histologycalstructure during different phases of the estrous cycle occurs.____________________________________________________________________________________________________________________Key words: histology, ovary, aceh cattle, estrous cycle